Relationship Between Mean Platelet Volume Elevation And Left Ventricular Mass Index in Hypertensive Patients - Yavuzkir, M.; Kurtoglu, E.; Yilmaz, M.; Korkmaz, H.; Cakmak, T.; Uysal, A.; Akbulut, M. (Excerpta Medica Inc-Elsevier Science Inc, 2014)
[Abstract Not Available]